Molecular cytogenetics and its contribution to the understanding of the chromosomal diversification in Hoplias malabaricus (Characiformes) - Vitorino, C. A.; Souza, I. L.; Rosa, J. N.; Valente, G. T. [UNESP]; Martins, C. [UNESP]; Venere, P. C. (Wiley-Blackwell, 2011)
Cytogenetic markers were used to compare the karyotypes of an isolated population of Hoplias malabaricus with others previously described. The results revealed peculiar characteristics that indicate a new independent evolutionary unit within the H. malabaricus complex.
Keywords: chromomycin A(3); FISH; karyomorphs